Avaliação da atividade vitivinícola na Serra Gaúcha com vistas à elaboração de inventários do ciclo de vida da cadeia produtiva - Dal Molin, Naiara (My University, 2021)
The viticulture and winery activities are highly representative in the southern region of Brazil, with potential impacts on the environment from the grape growing phase to the disposal of product packaging. The assessment of impacts can occur in different ways and the Life Cycle Assessment (LCA) is one of the tools that allow the assessment of environmental impacts at all stages of the production life cycle, thus helping to improve processes and products. In this context, this study objectifies to evaluate the viticulture and wine activities in the municipalities of Bento Gonçalves and Flores da Cunha, with a view to subsidizing the creation of life cycle inventories (LCI) of the wine producing chain. Data collection was carried out in loco in 71 viticulture properties and through documentary research in environmental licenses of 94 wineries. The characterization of properties and wineries took to into account a number of aspects such as: areas, water and energy consumption, sanitary sewage, solid waste generation, produced varieties, vine management, production purpose, consumption of raw materials and inputs, between others. The results found show that for the production of a bottle of wine, 1.07 kg of grapes are consumed and 17% of this amount is generated from bagasse, 4% from stalks and 2% from lees. Furthermore, water consumption for the production of grapes is 0.045 m³, while for the production of wine it is 0.00137 m³. Grape cultivation showed differences related to the cultivated grape varieties, mainly in relation to the pesticides used in each one. The data collected in environmental licenses showed great variation, especially among companies of different sizes. Data collection and treatment were the phases that involved the greatest degree of difficulty, especially in relation to primary data collection and calculation procedures. The characterization of properties and wine industries presented significant data for the construction of a database with a view to subsidizing the LCI oh the wine sector. The results, however, point to the need for greater depth and analysis so that the data are as representative as possible for LCA studies in a region. The results found still point to countless possibilities for future studies for which this study can serve as a basis. [resumo fornecido pelo autor]
A atividade vitivinícola tem grande representatividade na região Sul do Brasil com potenciais impactos ao meio ambiente desde a fase de cultivo da uva até o descarte de embalagens dos produtos. A avaliação dos impactos pode ocorrer de diferentes formas sendo a Avaliação do Ciclo de Vida (ACV) uma das ferramentas que permitem avaliar os impactos ambientais em todas as etapas do ciclo de vida de produção, auxiliando assim, na melhoria de processos e produtos. Nesse contexto, esse trabalho objetivou avaliar a atividade vitivinícola nos municípios de Bento Gonçalves e Flores da Cunha, com vistas a subsidiar a criação de inventários do ciclo de vida (ICV) da cadeia vitivinícola. A coleta de dados foi realizada in loco em 71 propriedades vitícolas e por meio de pesquisa documental em licenças ambientais de 94 vinícolas. A caracterização das propriedades e empresas levou em consideração uma série de aspectos como: áreas, consumo de água e energia, esgotamento sanitários, geração de resíduos sólidos, variedades produzidas, manejo das videiras, finalidade da produção, consumo de matéria prima e de insumos, entre outros. Os resultados encontrados evidenciam que para a produção de uma garrafa de vinho são consumidas 1,07 kg de uva e são gerados 17% desse valor de bagaço, 4% de engaço e 2% de borra. Além disso o consumo de água para a produção de uva é de 0,045 m³, enquanto para a produção de vinho é de 0,00137 m³. O cultivo da uva apresentou diferenças relacionadas às variedades de uva cultivadas, principalmente em relação aos agrotóxicos utilizados em cada uma. Os dados coletados nas licenças ambientais apresentaram grande variação, principalmente entre empresas de portes distintos. A coleta e o tratamento dos dados foram as fases que envolveram maior grau de dificuldade, principalmente em relação à coleta de dados primários e aos procedimentos de cálculos. A caracterização das propriedades e indústrias vinícolas apresentou dados significativos para a construção de base de dados com vistas a subsidiar o ICV do setor vitivinícola. Os resultados, no entanto, apontam para a necessidade de maior aprofundamento e análise de forma que os dados sejam os mais representativos possível para estudos de ACV de uma região. Os resultados encontrados ainda apontam inúmeras possibilidades de estudos futuros para os quais este estudo poderá servir de base. [resumo fornecido pelo autor]
Keywords: Vinho e vinificação - Serra, Região (RS); Uvas - Cultivo; Ciclo de vida do produto; Wine and wine making - Serra, Region (Brazil); Grapes - Cultivation; Product life cicle